ESTIMATION OF YIELD LOSS IN SUGARCANE (SACCHARUM SPP.) DUE TO EFFECTS OF SMUT DISEASE IN SOME SELECTED SUGARCANE GENOTYPES UNDER SUDAN CONDITIONS - P.W., Marchelo-d ’Ragga, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This study was conducted at Sugarcane Research Centre, Guneid, (Latitude 150 N, longitude 330E) in 2008/2009 cropping season. The objective was to estimate the amounts of losses (field and factory) incurred on sugarcane by the effects of smut disease of sugarcane caused by Ustilago scitaminea (Syd.). Replicated cane stalk samples were taken from each of three cane categories namely, whip-bearing canes from diseased stools (WBC-DS), apparently healthy looking canes from diseased stools (AHC-DS) and healthy canes from healthy stools (HC-HS) from some selected sugarcane genotypes. Results showed significant reductions of 5%, 4%, 5% and 40% forbrix, sucrose content (pol %), estimated recoverable sugar (ERS) and stalk weight at (P=0.05), respectively in comparison to healthy canes. Fibre content of whip bearing cane stalks was significantly higher by 7% to that of HC-HS and AHC-DS; this is detrimental and responsible for losses in ERS. Moisture content and purity were however, found to be unaffected by the disease. This study has showed that, smut disease incurs losses to most cane yield parameters both in the field and factory. Therefore, cane growers need to properly manage this disease, the most feasible would be through the propagation and use of resistant/ tolerant sugarcane genotypes to the disease augmented by crop sanitation to maintain low levels of inoculum.